2001
DOI: 10.1046/j.1439-0442.2001.00389.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Gastrin Activity and the Diagnosis of Bleeding Abomasal Ulcers in Cattle

Abstract: The present study was designed to evaluate the usefulness of plasma gastrin determinations as a diagnostic aid and to review the clinical and haematological findings in cattle with bleeding abomasal ulcers. Twenty-nine cows with bleeding abomasal ulcers and six healthy cows were used. Clinical and laboratory examinations, including plasma gastrin levels, were performed. Anorexia, depression, dark-coloured to black faeces, pale mucous membranes, abdominal pain, moderate tachycardia and tachypnoca were the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 10 publications
3
12
0
2
Order By: Relevance
“…In agreement with the findings of a recent report on cows with type-4 abomasal ulcers, 7 which cause diffuse peritonitis, type-3 ulcers occurred predominantly in the first four weeks after calving. 10,17,21,22,27 Of 145 cows with type-2 ulcer, which is associated with severe haemorrhage, 36% were diagnosed in the first four weeks of lactation. 8 A recent review of ulcerogenic factors 19,20 concluded that they consist of various stressors that act on cows in addition to the stress that surrounds parturition causing increased secretion of cortisol, hydrochloric acid and pepsin and decreased secretion of prostaglandin E. 19,20 Owners of cows that had been slaughtered and diagnosed with abomasal ulcers were unable to identify definitive causative factors.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the findings of a recent report on cows with type-4 abomasal ulcers, 7 which cause diffuse peritonitis, type-3 ulcers occurred predominantly in the first four weeks after calving. 10,17,21,22,27 Of 145 cows with type-2 ulcer, which is associated with severe haemorrhage, 36% were diagnosed in the first four weeks of lactation. 8 A recent review of ulcerogenic factors 19,20 concluded that they consist of various stressors that act on cows in addition to the stress that surrounds parturition causing increased secretion of cortisol, hydrochloric acid and pepsin and decreased secretion of prostaglandin E. 19,20 Owners of cows that had been slaughtered and diagnosed with abomasal ulcers were unable to identify definitive causative factors.…”
Section: Discussionmentioning
confidence: 99%
“…In adult cattle and in beef cattle, occurrence of abomasal damage differs between seasons. In adult dairy cattle, this could be related to the seasonality of milk production, because most ulcers develop around parturition, a period marked by stress and a severe change in diet (Smith et al, 1983;Sanford and Josephson, 1988;Ok et al, 2001;Tharwat and Ahmed, 2012). In beef calves, bad weather has often been proposed as a contributing factor (Jensen et al, 1976;Lilley et al, 1985;Mills et al, 1990;Marshall, 2009).…”
Section: Seasonal Effectsmentioning
confidence: 99%
“…Gastric ulcers regularly occur in calves and adult cattle, with an incidence varying between 2 and 87% (52,96,117,163,206,239). "Candidatus Helicobacter bovis" has been demonstrated in the pyloric part of the abomasums of calves and adult cattle but has not yet been cultivated in vitro (44).…”
Section: Gastric Helicobacters Associated With Ruminantsmentioning
confidence: 99%